Intuitionistic fuzzy 2-absorbing semiprimary ideals of commutative rings - Onar, Serkan; Yavuz, Sanem; Ersoy, Bayram Ali; Hila, Kostaq (TAYLOR & FRANCIS LTD, 2022)
The aim of this paper is to define intuitionistic fuzzy 2-absorbing semiprimary ideals and to give their properties. Also, we represent image and inverse image of intuitionistic fuzzy 2-absorbing semiprimary ideal. Furthermore, we provide some properties of cartesian product and give equivalent case for IF2ASPI.
Keywords: Intuitionistic fuzzy set; Intuitionistic fuzzy ideal; Intuitionistic fuzzy 2-absorbing ideal; Intuitionistic fuzzy 2-absorbing semiprimary ideal; PRIME IDEALS; Mathematics